Electro-acupuncture for central obesity: a patient-assessor blinded, randomized sham-controlled clinical trial - Tsz Fung Lam; Zipan Lyu; Xingyao Wu; Yi Ping Wong; Peihua Cao; Emily Yen Wong; Hung Bun Hung; Shiping Zhang; Zhaoxiang Bian; Linda L. D. Zhong (BMC, 2024)
Abstract Background Central obesity is considered as a significant health threat to individuals. Scientific research has demonstrated that intra-abdominal fat accumulation is associated with higher metabolic and cardiovascular disease risks independent of Body Mass Index (BMI). This study aimed to evaluate the efficacy and safety of electro-acupuncture in treating central obesity compared with sham acupuncture. Method This was a patient-assessor blinded, randomized, sham-controlled clinical trial. One hundred sixty eight participants aged between 18 and 65 years old with BMI ≥ 25 kg/m2 and waist circumference (WC) of men ≥ 90 cm / women ≥ 80 cm were enrolled and allocated to the acupuncture or sham acupuncture group equally. For the acupuncture group, disposable acupuncture needles were inserted into eight body acupoints, including Tianshu (ST-25), Daheng (SP-15), Daimai (GB-26), Qihai (CV-6), Zhongwan (CV-12), Zusanli (ST-36), Fenglong (ST-40), and Sanyinjiao (SP-6) with electrical stimulation. For the control group, Streitberger's non-invasive acupuncture needles were utilized at the same acupoints with identical stimulation modalities. The treatment duration was 8 weeks with 2 sessions per week and the follow-up period was 8 weeks. The primary outcome was the change in WC before and after the treatment. The secondary outcomes were the changes in hip circumference, waist-to-hip circumference ratio, BMI, and body fat percentage during the treatment and follow-up period. Results The acupuncture group displayed a significant change in WC compared to the sham group both treatment and follow-up period (MD = -1.1 cm, 95% CI = -2.8 to 4.1). Significant change in body fat percentage was recorded for both groups after treatment but no significance was observed during the follow-up period (MD = -0.1%, 95% CI = -1.9 to 2.2). The changes in hip circumference were also significant both treatment and follow-up period for the acupuncture group (MD = -2.0 cm, 95% CI = -3.7 to -1.7). Compared with sham acupuncture, the body weight (MD = -1 kg, 95% CI = -3.3 to 5.3), BMI (MD = -0.5, 95% CI = -0.7 to 1.9) also decreased significantly within and between groups. The incidence of adverse events was similar in the two groups. Conclusion This study provided evidence that electro-acupuncture could be effective in treating central obesity by reducing WC, hip circumference, body weight, BMI, and waist-to-hip circumference ratio. Trial registration ClinicalTrials.gov Identifier: NCT03815253, Registered 24 Jan 2019.